2023
DOI: 10.1186/s12889-022-14943-7
|View full text |Cite
|
Sign up to set email alerts
|

Orthorexia nervosa in gay men—the result of a spanish-polish eating disorders study

Abstract: Background The purpose of this exploratory study was to identifying demographic factors and unique predictors of ON e.g., the use of pre-exposure prophylaxis (PrEP), the use of social media and the Grindr ® dating application among a sample group of Spanish and Polish identifying gay men. Methods The study was conducted in Poland and Spain between March and June 2021 using questionary: ORTO-15. Data was collected using a three-section self-administ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…In this systematic review and meta-analysis, 34 studies used the <35 cutoff point [ 20 , 29 , 30 , 33 , 37 , 38 , 40 , 41 , 46 , 49 , 55 , 56 , 59 , 60 , 64 - 67 , 69 - 71 , 73 - 77 , 81 - 84 , 88 , 90 , 92 , 93 , 96 ], 64 studies used the <40 cutoff point [ 10 , 20 , 29 - 39 , 42 - 45 , 47 - 54 , 56 - 58 , 61 - 65 , 68 , 70 , 72 - 76 , 78 - 101 ], and 23 studies used both cutoff points [ 20 , 29 , 30 , 33 , 38 , 49 , 56 , 64 , 65 , 70 , 73 - 76 , 81 - 84 , 88 , 90 , 92 , 93 , 96 ]. Based on the <35 cutoff point, all the studies were cross-sectional.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this systematic review and meta-analysis, 34 studies used the <35 cutoff point [ 20 , 29 , 30 , 33 , 37 , 38 , 40 , 41 , 46 , 49 , 55 , 56 , 59 , 60 , 64 - 67 , 69 - 71 , 73 - 77 , 81 - 84 , 88 , 90 , 92 , 93 , 96 ], 64 studies used the <40 cutoff point [ 10 , 20 , 29 - 39 , 42 - 45 , 47 - 54 , 56 - 58 , 61 - 65 , 68 , 70 , 72 - 76 , 78 - 101 ], and 23 studies used both cutoff points [ 20 , 29 , 30 , 33 , 38 , 49 , 56 , 64 , 65 , 70 , 73 - 76 , 81 - 84 , 88 , 90 , 92 , 93 , 96 ]. Based on the <35 cutoff point, all the studies were cross-sectional.…”
Section: Resultsmentioning
confidence: 99%
“…According to sex, 64 studies reported the overall proportion of ON symptoms in both men and women [ 10 , 29 - 38 , 40 - 44 , 46 - 50 , 53 - 55 , 57 - 59 , 61 - 68 , 71 , 73 - 91 , 93 - 101 ], and nine studies only included one sex (i.e. only women [ 39 , 45 , 51 , 52 , 60 , 70 , 72 , 92 ] or men [ 69 ]). The remaining two studies [ 20 , 56 ] did not report proportions stratified by sex.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Authors found that use of the Grindr application was a significant predictor of orthorexia nervosa, whereas use of Instagram decreased the risk. Grindr usage is associated with body image distortion and feelings of sexual objectification, weight stigma, and social comparisons ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Different methods of measuring it, such as the participants’ skinfolds, waist circumference, or waist-to-hip ratio, would be interesting to study. An additional limitation is that we did not explore the effect of the use of social media [ 95 ] or dating apps [ 96 ], presented as significant risk factors for ON by other investigators.…”
Section: Discussionmentioning
confidence: 99%